2010
DOI: 10.1016/j.soildyn.2010.07.001
|View full text |Cite
|
Sign up to set email alerts
|

A 2.5D coupled FE-BE model for the prediction of railway induced vibrations

Abstract: Ground vibrations induced by railway traffic at grade and in tunnels are often studied by means of two-and-half dimensional (2.5D) models that are based on a Fourier transform of the coordinate in the longitudinal direction of the track. In this paper, the need for 2.5D coupled finite element-boundary element models is demonstrated in two cases where the prediction of railway induced vibrations is considered.A recently proposed novel 2.5D methodology is used where the finite element method is combined with a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
80
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 179 publications
(85 citation statements)
references
References 34 publications
(49 reference statements)
0
80
0
5
Order By: Relevance
“…The corresponding two-dimensional problem is solved for each wavenumber and an inverse Fourier transform is used to recover the three-dimensional response. This so-called 2.5D method is computationally more efficient than a full threedimensional approach and has been widely used for railway vibration [22,23,26,27].…”
Section: 5d Finite Element / Boundary Element Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The corresponding two-dimensional problem is solved for each wavenumber and an inverse Fourier transform is used to recover the three-dimensional response. This so-called 2.5D method is computationally more efficient than a full threedimensional approach and has been widely used for railway vibration [22,23,26,27].…”
Section: 5d Finite Element / Boundary Element Approachmentioning
confidence: 99%
“…As part of this study, a benchmark comparison has been made between the models used here and a similar approach used by KU Leuven [27]. In that approach the BE model is based on 2.5D Green's functions of a horizontally layered half-space [29].…”
Section: 5d Finite Element / Boundary Element Approachmentioning
confidence: 99%
“…The current prediction methods mostly hide the excitation forces in a black-box prediction from track irregularities. 15 The presentation of excitation forces is advantageous for the prediction of ground vibration as well as for the evaluation of the reduction effect of elastic track elements. 16,17 It can be observed that the soil is often disregarded if the vehicle-track interaction is in focus, 18 and that the excitation force is not usually analyzed if the wave propagation through the soil is in focus.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research over the topic allowed stablishing a consolidated pattern of behavior of the physical phenomena [4]: i) the train-track interaction mechanism gives rise to the source of excitation; ii) the energy is transferred to the surrounding ground and travels as elastic waves; iii) the vibrations can impinge nearby structures giving rise to annoyance of inhabitants [5,6]. Following this main pattern of behavior, several studies have been done regarding surface railway lines, deserving a special reference the studies conducted by the research group of K.U Leuven [7][8][9], by Alves Costa et al [10][11][12][13] and by Kouroussis et al [14], among others. Despite the huge research effort putted on the topic of vibrations induced by surface and underground railway infrastructures, all the studies were been confined to those classical cross-section configurations, i.e., surface lines or underground lines.…”
Section: Introductionmentioning
confidence: 99%